Late relapse in patients with diffuse large B‐cell lymphoma: impact of rituximab on their incidence and outcome. (5th August 2019) - Vannata, Barbara; Conconi, Annarita; Winkler, Jonas; Cascione, Luciano; Margiotta Casaluci, Gloria; Nassi, Luca; Moia, Riccardo; Pirosa, Maria Cristina; Moccia, Alden A.; Stathis, Anastasios; Rossi, Davide; Gaidano, Gianluca; et al.
Summary: Diffuse large B‐cell lymphoma (DLBCL) constitutes 25–35% of all non‐Hodgkin lymphomas in Western countries. Approximately two thirds of the patients can be cured with standard immuno‐chemotherapy. Most relapses occur within 1–2 years from diagnosis, however, the occurrence of relapses after 5 years or more has been described. We aimed at defining the incidence and clinical features of late relapses. Data of 1113 DLBCL patients were analysed. Among the 196 patients relapsing after a first complete remission, 36 (18% of relapses and 3% of all DLBCLs) experienced a recurrence more than 5 years from diagnosis. Late relapsing patients, in comparison with those relapsing earlier, showed a more favourable risk profile at presentation: normal lactate dehydrogenase levels ( P = 0·002), early Ann Arbor stage ( P = 0·006) and low International Prognostic Index ( P = 0·003). The risk of late relapse was lowered by the introduction of rituximab as part of the front‐line treatment ( P < 0·001). Cause‐specific survival (CSS) from the time of relapse was significantly better for late relapsing patients compared to those relapsing early: 5‐year CSS rates were 53% and 31%, respectively ( P = 0·033). A trend toward a better overall survival was also observed, with 5‐year rates after relapse of 47% and 25%, respectively ( P = 0·054).